Jerusalem and Malaita: The Visions and Prophecies of George Umai of West Kwara'ae, Malaita, Solomon Islands. Issue 3 (2nd November 2015) - Brown, Terry M.
Abstract: In this paper I examine the visions and teachings of George Umai (c.1938–1998), an Anglican lay leader of West Kwara'ae, Malaita, Solomon Islands. In his prophecies, Umai traced Malaitans, Solomon Islanders, and many other Oceanic peoples to his ancestors who he claimed fled from Jerusalem to Malaita in CE62. According to Umai, they brought the Ark of the Covenant from the Jerusalem Temple to Kwara'ae, Malaita where they buried it. I examine Umai's vision of the Ark of the Covenant and its apocalyptic and theocratic significance for Malaita and the world. In Umai's visions, teachings, and practice, Malaitan, Jewish, and Christian genealogy, apocalypse, and theocracy came together in a distinctive ethno‐theology that paralleled similar and prefigured later religious movements in Malaita but was too idiosyncratic to sustain.